MANAGEMENT STRATEGIES FOR AI-INTEGRATED CRAFT INDUSTRIES - Kale, Chaitrali Dilip; Kaur, Gurpreet; Sule, Bipin; Jarad, Rajendra Subhash; Prabha D; Bawa, Daljeet Singh; Priyadharshini K (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Traditional craft industry is crucial in preserving culture, rural livelihoods, and creative economies but continues to encounter the same issues with fragmentation of value chains, lack of market confidence, loss of skills and the inability to be sustainable. Artificial intelligence (AI) brings fresh possibilities to overcome these issues, but there is a need to use it in craft ecosystems mindfully, so as to prevent a degradation of culture and marginalization of artisans. This paper looks at AI implementation in craft industries and how to manage these industries, presenting the argument that the main challenge of implementing AI in craft industry is management and governance-related, and not a technological issue. The paper suggests a conceptual model that places strategic management in the mediating role between the traditional craft foundations and the AI capabilities. In the systematic discussion on the strategic alignment, human and AI work, operational integration, and ethical governance, the study proves that AI could be used to improve coordination, quality assurance, market responsiveness, and sustainability without compromising cultural authenticity. The operational mappings and pictorial performance analyses also indicate that the balanced improvement of supply-chain functions through the use of phased and collaborative AI adoption models is still possible without losing handcrafted variability. The results reported add up to strategic management and creative industry publications by reshaping AI as a supplementary technology that enhances the power of artisans instead of eliminating them. The article also brings out the significance of governance systems in respect to intellectual property, ownership of data and representation of cultures. Further studies must apply the suggested frameworks to different craft settings empirically and research involved design strategies of participatory AI development to create inclusive innovation.